The Role of English Language Use on Social Media and Peer Pressure: A Study of Youths’ Moral Decline in Osun State - Obadare, Felicia (Journal of Education Method and Learning Strategy, 2025)
The moral decline among Nigerian youths has increasingly raised concerns, with social media and peer pressure frequently identified as major contributing causes. This study examines how English language usage in these two factors influence behavioural patterns and affect society ideals. The study adopted a descriptive research design of survey type. The research was carried out in Osun State Nigeria. The sample size for the study comprised a total of 385 respondents. The study employed a random sampling technique to select male and female participants from six towns within the 3 Senatorial Districts in Osun State. A self-structured questionnaire of four point Likert scale on social media influence, peer pressure and moral decadence were used as instruments for data collection for the study. The validity and reliability of the instrument were ascertained through a pilot test. Research questions were answered using means and descriptive statistics, while the hypotheses were tested using linear regression analysis. The findings of the study revealed that social media has strong influence on the moral values of Nigerian youths. Also, the study established that peer pressure affects the behavioural patterns of Nigerian youths. Furthermore, the findings reveal a strong correlation between excessive social media usage, peer influence, and the decline in moral standards at β = 3.47 (n = 385) and F-statistic (F = 121.54, p < 0.05). The study concludes that social media and peer pressure significantly contribute to moral decadence among Nigerian youths. It was recommended that to mitigate the combined societal impact of social media and peer pressure on moral decadence, the government and relevant stakeholders should enforce strict regulations on media content while supporting community-based initiatives, that promote value-based education and youth empowerment programs.